Dalalah al-Alfazh in Hanafi Legal Theory: An Analysis of Explicit and Implicit Textual Indications - Mulyadi; Nofik Afriko; Mursal; Abdul Halim Hanafi (Islamic Studies and Education Journal, 2026)
This study examines the concept of Dalalah al-Alfazh within the framework of Hanafi usul al-fiqh, focusing on the four principal forms of textual indication: al-‘Ibarat al-Nash, al-Isyarat al-Nash, Dalalah al-Nash, and al-Iqtida’ al-Nash. The study aims to analyze the conceptual foundations, methodological characteristics, and legal implications of these categories in the process of Islamic legal derivation (istinbat al-ahkam). Employing a qualitative approach through descriptive-analytical library research, the study explores classical and contemporary works of Islamic legal theory to examine how Hanafi jurists interpret scriptural texts through linguistic and rational methodologies. The findings reveal that al-‘Ibarat al-Nash represents explicit textual meaning, while al-Isyarat al-Nash reflects implicit meanings derived from linguistic structure and logical implication. Dalalah al-Nash extends legal rulings to analogous cases based on shared legal causes (‘illah), whereas al-Iqtida’ al-Nash identifies implied meanings required for the coherence and operability of legal texts. These categories demonstrate the methodological sophistication of the Hanafi school in integrating textual interpretation, rational analysis, and the objectives of Islamic law (maqasid al-shari‘ah). The study further argues that the theory of Dalalah al-Alfazh remains highly relevant in addressing contemporary legal issues, particularly in contexts requiring adaptive and contextual Islamic legal reasoning. Therefore, understanding the various forms of textual indication is essential for developing a comprehensive, dynamic, and methodologically accountable approach to contemporary Islamic jurisprudence.